Investigation on Aging of Metallic Surface Integrated Micro-POFs. (2016) - Hachicha, B.; Overmeyer, L.
Abstract: Surface integrated optical waveguides present a possibility to realize inherent communication structures. Optical communication is used particularly by smart parts exposed to humidity, high vibration or electromagnetic fields. We developed a method to integrate micro-polymer optical fibers ( μ -POFs) into metallic surfaces using the dispensing process. After positioning, the μ -POFs are bonded to the surface by dispensing UV-curing adhesives. The bonded optical waveguide is coupled at its end-facets respectively to sender or receiver elements. Efficiency of the coupling depends on the alignment stability of the polymer fiber to beam sender or receiver. In operating conditions the smart parts undergo aging due to thermal and mechanical stress. We investigated the possible influence of this aging on the position stability of bonded μ -POFs, and consequently on the optical communication efficiency. The experimental set-up as well as the measurements are presented and discussed in this article.